2015
DOI: 10.1523/jneurosci.2659-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of Face-Selective Regions in the Extrastriate Visual Cortex of the Marmoset

Abstract: The cerebral cortex of humans and macaques has specialized regions for processing faces and other visual stimulus categories. It is unknown whether a similar functional organization exists in New World monkeys, such as the common marmoset (Callithrix jacchus), a species of growing interest as a primate model in neuroscience. To address this question, we measured selective neural responses in the brain of four awake marmosets trained to fix their gaze upon images of faces, bodies, objects, and control patterns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
125
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 67 publications
(10 reference statements)
18
125
1
1
Order By: Relevance
“…Data presented in this study suggest that marmosets may be particularly valuable as a model system for application of optogenetic techniques in studies of primate brain function. These methods can be combined with existing behavioral (Chow et al 2015;Miller and Thomas 2012;Mitchell et al 2014;Osmanski et al 2013;Remington et al 2012), neurophysiological (Bendor and Wang 2005;Eliades and Wang 2008;Miller et al 2015;Wang et al 2005), and neuroimaging approaches (Hung et al 2015;Liu et al 2013;Silva et al 2011) in marmosets to more precisely test the functional architecture underlying primate behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented in this study suggest that marmosets may be particularly valuable as a model system for application of optogenetic techniques in studies of primate brain function. These methods can be combined with existing behavioral (Chow et al 2015;Miller and Thomas 2012;Mitchell et al 2014;Osmanski et al 2013;Remington et al 2012), neurophysiological (Bendor and Wang 2005;Eliades and Wang 2008;Miller et al 2015;Wang et al 2005), and neuroimaging approaches (Hung et al 2015;Liu et al 2013;Silva et al 2011) in marmosets to more precisely test the functional architecture underlying primate behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Examination into the evolution of cortical networks specialized for face processing has largely relied on comparisons between macaques and humans [1] (Figure 1). A recent paper [2] adds another species to the mix, the common marmoset, whose evolutionary origin is about 10 million years prior to macaques. In combination with recent studies in macaques examining the location of face patches relative to retinotopic areas [3] and natural face motion [4], we are beginning to understand the anatomical and functional features contributing to similarities and differences of the face network across species.…”
mentioning
confidence: 99%
“…Specifically, using both electrocorticography (ECoG) and fMRI, Hung and colleagues [2] found that the face network in marmosets consists of six distributed face patches. The anatomical topology of these patches was consistent across methodologies and individual marmosets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marmosets have well developed frontal and temporal lobes (e.g. Roberts et al, 2007 ;Burman and Rosa, 2009 ;Hung et al, 2015 ), a sophisticated visual cortex (e.g. Solomon and Rosa, 2014 ;Mitchell and Leopold, 2015 ), multiple cortical areas involved in planning and execution of movements (e.g.…”
Section: Introductionmentioning
confidence: 99%